Using means-end theory to understand technology acceptance: a systematic literature review - Mol, Artur Martins; Machado, Mônica da Consolação; Ishitani, Lucila (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Means-end chains consist of a sequence of attributes, consequences, and values. These attributes can be understood as characteristics of a product; the consequences can be seen as benefits arising from this product's use; the values represent the end goals important to the consumer or the motivation to use the product. Means-end chain analysis originates in marketing and relates consumers and products. In the context of systems, what drives a product to be accepted by users. Problem: To understand the application of the means-end theory in the IS area to identify factors that lead to user acceptance of a system. Solution: To conduct a Systematic Literature Review (SLR) to understand how means-end theory helped understand user acceptance of technology. IS Theory: This work was inspired by the Technology Acceptance Model Theory, which helps to determine an individual's intention to use a system. Methodology adopted: The SLR searched for scientific articles published in the last five years that contained the keywords “means-end”, “technology adoption”, “technology acceptance”, “technology resistance”, “user adoption”, “user acceptance” and “user resistance”. The search was carried out in the databases of ACM, Elsevier (ScienceDirect), and IEEE, and also by Google Scholar. Summary of results: 13 articles were selected. From the analysis of these articles, we extracted guidelines on data collection, number of recommended participants, indicators of data reliability, and data analysis. Contribution and Impact in the IS area: The results can benefit further studies applying means-end theory for analysis and survey of software requirements, particularly considering the most important values for end users.